Improving Students' Digital Literacy Through GPT Chat-Based AI Usage Training at State Vocational School 6 Bulukumba - Andi Muhammad Idkhan; Sudarmanto Jayanegara; Ramli Rasjid; Samnur; Ahmad Risal Abdullah (Sakura Digital Nusantara, 2026)
The development of digital technology requires students to have strong digital literacy skills to be able to use technology wisely, creatively, and productively. However, the use of artificial intelligence (AI)-based technology, particularly Chat GPT-based applications, is still not optimal in vocational high schools. This community service activity aims to improve students' digital literacy through training in the use of Chat GPT-based AI at SMK Negeri 6 Bulukumba. The implementation method includes preparation, outreach, training, hands-on practice, and evaluation of participant understanding. The training materials covered an introduction to AI concepts, the use of Chat GPT in learning, prompt development techniques, and the ethical and responsible use of AI. The results of the activity indicate an increase in students' understanding and skills in using AI technology as a supporting medium for learning and information retrieval. Students became more active, creative, and able to utilize digital technology to complete academic assignments effectively. Furthermore, this activity also raised students' awareness of the importance of digital ethics in the use of AI. Therefore, training in the use of Chat GPT-based AI can be an effective strategy for improving students' digital literacy in vocational high schools.